Development of Near Space: Current Status, Problems, and Countermeasures - Junlin Yang; Chongwen Jiang; Ming Zhu; Zili Wang (中国工程科学)
The near space is crucial for national security; it is an important carrier for new combat forces and a new space domain for international cooperation and competition. By analyzing the significance of the near space, this study clarifies the new situation of near space development worldwide, summarizes the current status and existing problems of near space development in China, and proposes corresponding measures. Our research indicates that near space technologies are developing rapidly worldwide, countries around the world are continuously innovating in near space management exploration, and the global near space governance is accelerating. China leads the world in near space development in terms of technical strength, application strength, and support strength; however, it still faces some risks and challenges. Therefore, concerted efforts should be made from the following aspects: development strategy, key technology development and management, application technologies and engineering innovation, law guarantee, risk response, international governance, laboratory system construction, and talent cultivation, thereby enhancing the comprehensive competitiveness and influence of China in the field of near space.